SUBTROPICAL WATER MASSES IN HALMAHERA WATERS - Hadikusumah Hadikusumah (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2010)
Research of water masses by using conductivity temperature depth (CTD), are conducted in the eastern path of the Indonesia Throughflow (ITF) in the Halmahera, Seram and Banda seas during March-April 2007 under the Expedition of Widya Nusantara (EWIN). The objective of this research is to see maximum salinity spread of South Pacific Subtropical Water (SPSW) water masses enter the eastern Indonesia Waters. The temperature and salinity profiles show the presence of the presence of SPSW have been very much confined to the Halmahera Sea only. Little of this water masses have been detected in the eastern Seram Sea, but none in Banda Sea. Early data of Arlindo Mixing (ARMIX) experiment in southeast monsoon 1993 indicated that this water masses SPSW may entered the southern most part of the Moluccas Sea. Type of South Pacific Subtropical Water (SPSW) water masses appears in the Halmahera Sea at an average depth of 200m and the dominant flows between Halmahera and Obi Islands (Moluccas Sea continues to the east). Type of South Pacific Intermediate Water (SPIW) water mass appeared on average Halmahera Sea at a depth of 750m and the dominant flows between Halmahera and Obi Islands (Moluccas Sea continues to the east). Type of North Pacific Subtropical Water (NPSW) water masses at an average depth of ~ 150m found in the northern part of Halmahera, the dominant flow to the Celebes Sea, Makassar Strait, Flores Sea and partly flows into Lombok Straits. Type of minimum salinity water mass of North Pacific Intermediate Water (NPIW) obtained at an average depth of ~ 400m dominant flow towards the Celebes Sea, Makassar Strait and Flores Sea.Keywords: maximum salinity, SPSW, Halmahera, Seram, and Banda Seas